Financial Performance Analysis in PT. Pegadaian (Persero) Using the Method Economic Value Added (EVA) - Annnisa Paramaswary Aslam; Dian Anggraece Sigit Parawansa (CV. Sakura Digital Nusantara, 2023)
This study aims to determine the financial performance of PT. Pegadaian (Persero) based on an analysis of Economic Value Added (EVA) for 2014 to 2017. The type of research used in this study is quantitative. The research population which is also a sample of research is the financial statements of the last four years (2014-2017). Data collection is done by means of documentation and interviews. Furthermore, it is analyzed using EVA analysis which consists of NOPAT analysis of Invested Capital WACC and Capital Charges. The results of this study show that the value of Economic Value Added (EVA) at PT. Pegadaian (Persero). In 2014-2017 it showed a positive value (EVA> 0) meaning that the company was able to create economic added value for the company so that the company was able to fulfill obligations and create profits for the company.